A dolphin fossil ear bone from the northern Neotropics–insights into habitat transitions in iniid evolution. Issue 3 (4th May 2017) - Aguirre-Fernández, Gabriel; Mennecart, Bastien; Sánchez-Villagra, Marcelo R.; Sánchez, Rodolfo; Costeur, Loïc
ABSTRACT: An iniid fossil (Cetacea, Odontoceti) is reported based on a periotic found in the Codore Formation (late Miocene to middle Pliocene) of northwestern Venezuela. The marine sediments where the Codore dolphin was collected have yielded another cetacean and a diverse elasmobranch fauna. Cladistic analysis indicates a close relationship between the Codore dolphin and the extant Amazon River dolphin ( Inia geoffrensis ); key characteristics include a large cochlear portion that is dorsoventrally compressed and the extremely small size of the posterior process. High-resolution micro-computed tomography scans were used for the description and analysis of the bony labyrinth endocast. Geometric morphometric analysis of the bony labyrinth endocast places the Codore dolphin as intermediate between the La Plata dolphin ( Pontoporia blainvillei ) and Inia geoffrensis (principal component 1), but distinctive from both extant species (principal component 2). Comparisons of the depositional environment with cladistically informed reconstructions and inferences based on cochlear and vestibular anatomy suggest that the Codore dolphin had the flexibility to enter marine, brackish, and fluvial environments as some extant cetaceans do today (e.g., Pontoporia blainvillei ). SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Aguirre-Fernández, G., B. Mennecart, M. R. Sánchez-Villagra, R. Sánchez, and L. Costeur. 2017. A dolphin fossil ear bone from the northern Neotropics—insights into habitat transitions in iniid evolution. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1315817.